Exploring lipid-protein interactions in plant membranes - Škrabálková, Eliška; Pejchar, Přemysl; Potocký, Martin (Journal of experimental botany, 2024)
Once regarded as mere membrane building blocks, lipids are now recognized as diverse and intricate players that mold the functions, identities, and responses of cellular membranes. Although the interactions of lipids with integral and peripheral membrane proteins are crucial for their localization, activity, and function, how proteins bind lipids is still far from being thoroughly explored. Describing and characterizing these dynamic protein-lipid interactions is thus essential to understanding the membrane-associated processes. Here we review the current range of experimental techniques employed to study plant protein-lipid interactions, integrating various methods. We summarize the principles, advantages, and limitations of classical in vitro biochemical approaches, including protein-lipid overlays and various liposome binding assays, and complement them with in vivo microscopic techniques centered around the use of genetically encoded lipid sensors and pharmacological or genetic membrane lipid manipulation tools. We also highlight several emerging techniques still awaiting their advancement into plant membrane research and emphasize the need to use complementary experimental strategies as key for elucidating the mechanistic roles of protein-lipid interactions in plant cell biology.
Keywords: lipid manipulation; peripheral membrane proteins; Membrane Lipids; rostliny; membránové proteiny; Plants; Membrane Proteins; Cell Membrane; protein–lipid interactions; membránové lipidy; Genetically encoded biosensors; microscopy; Plant Proteins; membrane lipid imaging; rostlinné proteiny; buněčná membrána